Analyzing Relationships Between Adolescents’ Cultural Identity and Narrativization in East Asian Music - Hannah, K. Shin (Journal of Human Psychology, 2025)
The formation of narratives while listening to music is seen across cultures, but narrative perception in Asian Americans who have bicultural identities is not well understood. This study analyzed the potential effect of cultural identity on adolescents’ ability to form narratives with East Asian music. Two groups of adolescents (n=42), Asian American (n=28) and Non-Asian American (n=14), listened to three music excerpts with varying degrees of Asian and Western influences. The most Asian-influenced excerpt was a Gugak Korean traditional piece titled T’ungae sanjo, performed on traditional Korean folk instruments and creating a distinctly East Asian sound. The Mixed excerpt, containing both Western and Asian influences, was from Tan Dun’s Eight Memories in Watercolor. It contained a Chinese folk melody while being performed on a Western instrument. Finally, the most Western-influenced excerpt was from Toru Takemitsu’s Rain Tree Sketch. The piece contained octatonicism, a musical technique prominent in modern Western composers’ works. Participants completed a survey containing a free response question where they described their imagined narratives and a survey containing 4 questions measuring narrative engagement. Chi-square tests, t-tests, and reflexive thematic analysis were used to yield the results from the data collected. Results demonstrated that the extent of narrativization was dependent on enculturation. Asian Americans, with their bicultural identities, demonstrated consistent narrativization across all excerpts. In contrast, non-Asian Americans narrativized significantly less for the traditional Asian excerpt. Within the free responses, both cohorts identified similar themes with the Western-influenced music, as they have had overlapping exposure to Western culture leading to shared thought patterns. However, there was substantial thematic variability between cohorts with the Asian-influenced music, as the two cohorts had different levels of exposure to Asian culture. This study thus reinforces the notion that enculturation has a profound effect on narrativization in music, demonstrated through Asian American adolescents’ abilities to narrativize to music containing both Asian and Western roots.
Keywords: Asian American adolescents; East Asian music; Music perception; Narrativization; Narrative engagement